English Mnemonic Lexicon: Constituent Structure and Verbalization Potential - Tivyaeva, Irina; Syomina, Olga (English Studies at NBU, 2020)
This paper presents a study of the system of lexical devices used by English speakers to verbalize their personal memory experiences. The approach presented in the paper presupposes inclusion of non-narrative structures into the spectrum of language forms conveying mnemonic meanings and extends the latter so as to encompass the meanings of encoding, storage, retrieval and loss. The research is based on the hypothesis that lexical units expressing memory-related meanings in English constitute a specifically organized system. A variety of communicative contexts representing mnemonic situations are analyzed as to develop a typology of memory verbalizers in English, estimate their functional potential and role in objectifying personal memory experiences on the lexical level. The results confirm the original hypothesis and suggest that mnemonic lexicon as a linguistic reflection of the mnemonic faculty is an important and largely understudied element of the language – memory system.